Technological transition in sugarcane hydroagricultural polygon and impacts on labor - Bento, Fredi Dos Santos [UNESP]; Thomaz Junior, Antonio [UNESP] (Edicions de la Universitat de Barcelona, 2021)
At the beginning of the 21st century, the offensive of capital on labor is increasingly expanding, driven by the insatiable need for accumulation / reproduction. In Brazil, among the various forms of personification of this model of society, we highlight sugar cane hydroagricultural. The main objective of this text, concerns the discussion of the main impacts on labor, such as total outsourcing, loss of rights, illness process and disposal of workers that occurred in the midst of the technological transition in the sugarcane fields, as we could see when we used semi-structured interviews with workers from the Sugarcane Hydroagricultural Polygon and their representative institutions, such as rural workers 'and workers' unions, in opposition to the discourse of improving their living conditions, promised with the advance of mechanization, revealing in reality, a process of systemic degradation of labor.
Transição tecnológica no polígono do agrohidronegócio canavieiro e os impactos sobre o trabalho
Keywords: Labor; Productive restructuring; Sugarcane hydroagricultural; Systemic labor degradation